1981
DOI: 10.1038/bjc.1981.143
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and promotion at different ages and doses in 2200 mice. III. Linear extrapolation from high doses may underestimate low-dose tumour risks

Abstract: Summary.-The dose-response relationships from the data described in Paper I were analysed. Among unpromoted animals, only doses sufficient to cause ulceration with subsequent promotion due to wound healing caused a rapid crop of tumours, so the dose-response curve exhibited strong upward curvature. Among promoted animals, the response of the skin to initiation appeared to have been nearly saturated by all DMBA doses tested, so that a 30-fold decrease in dose produced only a 3-fold decrease in effect. The dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Cross-talk between mesenchyme and epithelium has been described as a known driver of differentiation and development [82,83] [85]. Also, the average diameter of the tumors was larger in the older animals.…”
Section: Aging and Multi-stage Carcinogenesismentioning
confidence: 99%
“…Cross-talk between mesenchyme and epithelium has been described as a known driver of differentiation and development [82,83] [85]. Also, the average diameter of the tumors was larger in the older animals.…”
Section: Aging and Multi-stage Carcinogenesismentioning
confidence: 99%
“…Evidence that tumour cells may produce both autocrine and paracrine growth-stimulating substances has provided a possible mechanism for such interaction (Sporn & Roberts, 1985). In addition, there is evidence from both in vivo and in vitro experiments that initiation may be a more frequent event than transformation (Mondal & Heidelberger, 1970;Stenback et al, 1981); and that transformation of initiated cells in culture can be inhibited by co-culture with an excess of non-initiated cells (Haber & Thilly, 1978;Mordan et al, 1983). Both of these observations could be explained by mechamnsms involving interactions between initiated cells and their neighbours.…”
mentioning
confidence: 99%
“…In the liver, a nonlinear increase in tumor incidence can be observed when doses of genotoxic compounds are greater than or equal to cytotoxic doses (Scherer & Emmelot, 1975;Williams et al, 1999). In mouse skin tumorigenesis, Stenback and coworkers (Stenback et al, 1981) demonstrated that rapid tumor development only occurs at doses of genotoxic compounds that are cytotoxic. Under these conditions, response is related to the amount exceeding some cytotoxic threshold, not total dose or AUC.…”
Section: Analyzing Alternate Dose Metricsmentioning
confidence: 98%